First external quality assurance program for bloodstream Real-Time PCR monitoring of treatment response in clinical trials of Chagas disease - Ramirez, Juan C. (2017)
Fil: Ramírez, Juan C. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular Dr. Héctor N. Torres; Argentina.